2012
DOI: 10.1111/j.1460-9568.2012.08215.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical projections to primary visual cortex in anophthalmic, enucleated and sighted mice

Abstract: The purpose of this study was to identify and compare the afferent projections to the primary visual cortex in intact and enucleated C57BL/6 mice and in ZRDCT/An anophthalmic mice. Early loss of sensory-driven activity in blind subjects can lead to activations of the primary visual cortex by haptic or auditory stimuli. This intermodal activation following the onset of blindness is believed to arise through either unmasking of already present cortical connections, sprouting of novel cortical connections or enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 92 publications
5
62
0
Order By: Relevance
“…Several studies have shown that primary sensory cortices can respond to multisensory inputs (Clavagnier et al, 2004; Schroeder and Foxe, 2005; Shams et al, 2005; Ghazanfar and Schroeder, 2006; Kayser et al, 2007; Martuzzi et al, 2007; Mishra et al, 2007; Senkowski et al, 2007; Wang et al, 2008; Sperdin et al, 2009; Koelewijn et al, 2010; Raij et al, 2010). The underpinning anatomical substrate of multisensory integration was always assumed to be projections through white matter (Bizley et al, 2007; Lakatos et al, 2007; Bizley and King, 2009; Cappe et al, 2009; Larsen et al, 2009; Musacchia and Schroeder, 2009; Charbonneau et al, 2012; Laramee et al, 2013). Our study raises the possibility that at least part of multisensory interactions could be carried out by a diffuse projection system that directly connects unimodal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that primary sensory cortices can respond to multisensory inputs (Clavagnier et al, 2004; Schroeder and Foxe, 2005; Shams et al, 2005; Ghazanfar and Schroeder, 2006; Kayser et al, 2007; Martuzzi et al, 2007; Mishra et al, 2007; Senkowski et al, 2007; Wang et al, 2008; Sperdin et al, 2009; Koelewijn et al, 2010; Raij et al, 2010). The underpinning anatomical substrate of multisensory integration was always assumed to be projections through white matter (Bizley et al, 2007; Lakatos et al, 2007; Bizley and King, 2009; Cappe et al, 2009; Larsen et al, 2009; Musacchia and Schroeder, 2009; Charbonneau et al, 2012; Laramee et al, 2013). Our study raises the possibility that at least part of multisensory interactions could be carried out by a diffuse projection system that directly connects unimodal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to examine the anatomy and physiology of neurons in the thalamus and somatosensory cortex in Cdx1-Cre;Fz3 CKO/− mice to explore the fate of territories that normally process somatosensory information from the trunk and limbs. One might anticipate that there would be a large scale remapping of these territories analogous to the remapping of visual cortex in humans or animals that are congenitally blind (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of auditory activation of the primary visual cortex in the enucleated mice is surprizing considering that the visual cortex in intact and enucleated C57Bl/6J mice and ZRDCT/An mice receives similar extensive cortical auditory and somatosensory afferents (Charbonneau et al, 2012) as well as indirect corticocortical projections from the auditory cortex (Laramée et al, 2011). Moreover, auditory activation of the visual cortex was reported in enucleated hamsters (Izraeli et al, 2002), rats (Piché et al, 2007), opossum (Kahn and Krubitzer, 2002) and cats (Kahn and Krubitzer, 2002;Yaka et al, 2000Yaka et al, , 1999.…”
Section: 2mentioning
confidence: 97%
“…There is also evidence for crossmodal plasticity in that the visual cortex is activated by auditory stimuli in ZRDCT/An mice . This auditory activity could originate from a projection from the inferior colliculus to the lateral geniculate nucleus (Chabot et al, 2008) and from direct cortical connections between the auditory and visual cortex (Charbonneau et al, 2012).…”
Section: Introductionmentioning
confidence: 99%